Answers

2016-02-26T22:21:31+05:30
x= \frac{ e^{y}- e^{-y}  }{ e^{y} +  e^{-y}  }
Multiplying both side by ( e^{y} + e^{-y} )
x e^{y} +x e^{-y} =  e^{y} -  e^{-y} 

Rearranging
x e^{y} - e^{y} = -xe^{-y} - e^{-y}
Multiplying by -1
e^{y}-xe^{y}=xe^{-y}+e^{-y}
e^{y}(1-x)=e^{-y}(1+x)
 \frac{ e^{y} }{e^{-y}} = \frac{1+x}{1-x}
 e^{2y}= \frac{1+x}{1-x}
Taking log of base e on both sides
2y  log_{e} e=log_{e}( \frac{1+x}{1-x} )
But  log_{e}e=1
∴ y =  \frac{1}{2} log_{e} (\frac{1+x}{1-x} )
1 5 1
what do you mean by [tex] ?
Its a code of writing maths in HTML known as Latex....
Wait for some while or reload till the scripts are visible as equations..
Can you mark it as the brainliest........